Local Government in Europe : New Perspectives and Democratic Challenges - Teles, Filipe; Szmigiel-Rawska, Katarzyna; Lackowska, Marta (Book collections on Project MUSE., 2021)
Drawing on classical and emerging research perspectives, this comprehensive book provides an up-to-date review of local government in Europe. Featuring an impressive range of contributors from both eastern and western Europe, the book addresses three main topics: territorial reforms, democratic empowerment of citizens and the role of local leadership, as well as new trends in local finances. Acknowledging their inherent diversity, the book examines the ways that local governments have responded to shared challenges, such as climate change, increasing populism and democratic deficit in order to identify both the variety and communalities between the country-specific features. In doing so, it provides a rich picture of the latest trends in local government, as well as pointing the way for future developments.